EFEITO DA INCLUSÃO DE AÇÚCAR OU INOCULANTE BACTERIANO NA SILAGEM DE MILHO SOBRE PERDAS, VALOR NUTRICIONAL, EFICIÊNCIA ECONÔMICA E DESEMPENHO DE NOVILHOS CONFINADOS - Zanette, Paula Maria (2010)
The experiment was conducted at the Department of Animal Production (NUPRAN) State University Midwest (UNICENTRO), with the aim of evaluating corn silage with inclusion of sugar or bacterial inoculant, compared with the conventional, about loss, nutritional value, economic efficiency and performance of feedlot bulls. Were evaluated three treatments: T1 - no additives (conventional) T2 - with the addition of 2% DM of refined sugar trade, T3 - silage with bacterial taxa inclusion inoculant, comprising Enterococcus faecium, Lactobacillus plantarum, Pediococcus acidilatici, amylase, cellulase, hemicellulolytic enzime. In the superior stratum, the losses of dry matter, fiber in acid detergent and fiber in neuter detergent were higher, regardless of type of silage. The, silage with sugar had the lowest DM recovery (83.01%) compared to conventional silage (85.34%) and being silage with bacterial inoculant additives with the resulting higher recovery of DM in the silo (89%). For parameters of animal performance, no significant difference in medium dairy gain, dry matter intake, dry matter intake for live weigh and alimentary conversion, with mean values of 1.472kg.day-1, 9.42kg.day-1, 2.21% and 6.63 respectively, showing effect only for the period evaluation. The silages with additives had higher dry matter digestibility compared of silages with no additives (69.68 and 68.59 against 66.83%). For the parameters of behavior, the treatment did not affect the activities of animals for rumination, rest, food consumption, water consumption, frequency of liquid excreta, frequency of intake of food or water. Of the parameters evaluated in the housing, the use of silage additives in improved fat thickness, with higher levels in animals that were fed with silage with bacterial inoculant additives (4.7mm). As for the economic efficiency, the biggest response was obtuse, determined by a somatory of parameters, for the animals feed with the silage with bacterial inoculant, resulting in 26,46% more economic response for animal, compared with no application of additives.